Victims of Parental Kidnappings in Light of Polish Criminal Law (Based on the Results of Case Law Research) - Dajnowicz-Piesiecka, Diana (Kriminologijos studijos, 2018)
[full article, abstract in English; abstract in Lithuanian] This paper concerns the victims of parental abductions in Poland. The aim of the article is to present the victims of parental abductions in the light of the Polish criminal case law. The study has an empirical character because it presents the results of research carried out using a criminal case law analysis. The study included 59 criminal cases concerning the parental kidnapping of a child. The research revealed that the Polish law treats the person from whom the child was kidnapped as a victim of parental kidnapping. Interestingly, the child is not considered a victim. Based on the research, a conclusion was formulated that parental abductions are not only the result of disputes between the parents of a child, but that children can also be abducted from the care of other people, for example, the directors of orphanages or grandparents who look after the children. This article argues that parental abductions are not only a problem for families but also for institutions professionally involved in childcare.